Propuesta del proceso para la obtención de pectina partiendo de la cáscara de gulupa a escala piloto (2021)
In this degree work the proposal is made for the production of pectin from the gulupa peel, for this the pretreatments of washing with cold water, blanching for 10 minutes at 90 ° C, oven drying and size reduction were selected by means of an industrial blender. The extraction method proposed is the microwave and ultrasound assisted extraction (UMAE), for the ultrasound equipment a frequency of 40 kHz will be used for 20 minutes and the microwave equipment will handle a frequency of 2450 Hz for 10 minutes, conditions defined based on the bibliographic review and that are reported as having the highest performance.